Enhanced interfacial electron transfer kinetics between Co2+/3+ complexes and organic dyes with free space near their backbone. Issue 18 (28th April 2022) - Cho, Inseong; Dheendayal, Mantra; Wagner, Pawel; Mozer, Attila J.
Abstract : Enhanced electronic coupling is achieved by opening up appropriate free spaces near the π-conjugated backbone of organic dyes enhancing electron transfer rates by six times. Abstract : Fast electron transfer (ET) between surface-bound dye molecules and electron donor molecules dissolved in electrolytes with simultaneous reduction in recombination rates are crucial to improve the photon-to-electron conversion efficiency of photo-electrochemical technologies. Here, the electron transfer characteristics of a new dye molecule PX47 with only two alkyl chains placed in the anti configuration of the π-conjugated quarterthiophene backbone is studied. It is anticipated that the appropriate free space between the alkyl chains allowed the approach of the Co(c1-bpy)3 redox mediator to near the backbone of the dye anchored to a TiO2 electrode even at complete coverage of the TiO2 surface, thereby enhancing electronic coupling. The ET kinetics measured by transient absorption spectroscopy were enhanced by a factor of six between PX47 and Co(c1-bpy)3 as compared to the structurally similar MK2 dye with four alkyl chains. The ET rates between PX47 and the larger nonyl-substituted (Co(c9-bpy)3 or tert -butyl substituted Co bipyridine (Co(dtb-bpy)3 ) were reduced by half and one third as compared to Co(c1-bpy)3, respectively, indicating a blocking effect of longer or bulky substituents on the redox mediators. For MK2 with four alkyl chains near the backbone, the ET rate was very similar between Co(c1-bpy)3 and Co(dtb-bpy)3 and was enhanced for (Co(c9-bpy)3, the latter explained by trapping the mediator inside the dye layer due to alkyl–alkyl interactions. Unexpectedly, two distinctly different recombination rates were measured between the oxidized Co(c1-bpy)3 mediators and TiO2 electrons in the PX47-TiO2 samples, which is explained by two possible arrangements of the PX47 on the TiO2 surface. The dominant arrangement allowed the adsorption of Co(c1-bpy)3 on the TiO2 surface enhancing recombination. The findings suggest that by strategically placing alkyl chains around the electronic units of dye molecules, the redox mediator can be intercalated into the dye layer increasing proximity and better electronic coupling. Although this work presents an effective strategy to enhance ET rates by designing structurally complementary electron donor–acceptor pairs, additional design strategies to further reduce recombination in such open dye structures are needed.